A model for mobile learning non-functional requirement elicitation. (2016) - Sarrab, Mohamed; Baghdadi, Youcef; Al-Shihi, Hafedh; Bourdoucen, Hadj
Mobile learning (M-learning) applications are gaining high momentum and popularity in easing the learning process. However, engineering M-learning applications contain several challenges, specifically in terms of engineering requirements. Despite of a large amount of significant research in the field of M-learning, there is not much research focused on the requirements from a quality perspective, mainly the non-functional requirements that would allow the evaluation of M-leaning applications. This paper proposes a model that captures M-learning non-functional requirements from three dimensions: pedagogical and educational, social and cultural, and business and economical. This model allows the assessment of the quality of M-learning applications. Four different M-learning applications (Edmodo, Schoology, Moodle and Blackboard) have therefore been used to discuss the model. This effort is part of a number of expected outcomes of funded research project that investigate the development, adoption and dissemination of M-learning in Oman.